Effect of the Hospital Elder Life Program on Risk of 30‐Day Readmission. Issue 1 (31st October 2017) - Rubin, Fred H.; Bellon, Johanna; Bilderback, Andrew; Urda, Kevin; Inouye, Sharon K.
Abstract : Objectives: To compare rates of 30‐day readmission between hospital units with a Hospital Elder Life Program (HELP) and control units without HELP. Design: Retrospective cohort study. Setting: The study took place from July 1, 2013, to June 30, 2014, at the University of Pittsburgh Medical Center Shadyside, a 520‐bed community teaching hospital that has used HELP since 2002. Eight medical and surgical units with HELP were compared with 10 medical and surgical units without HELP. Participants: During the study period, HELP units, had 4, 794 patients aged 70 and older, and usual care units had 2, 834. Intervention: HELP is a multifactorial, multidisciplinary program that provides targeted interventions for delirium risk factors in at‐risk individuals in collaboration with bedside staff. Measurements: Mixed‐effects Poisson regression models were used to estimate the adjusted incident risk ratio for 30‐day readmission between HELP and usual care units for the overall cohort and for the subgroup of individuals discharged home, with or without services. Results: Patients on HELP units were more likely than those in usual care units to be older, female, and black and had an unadjusted readmission rate of 16.9%, versus 18.9% for patients on control units. The adjusted risk of readmission was 0.83 (95% confidence interval (CI) = 0.73–0.94, P = .003) for HELP unit patients overall and 0.74 (95% CI = 0.63–0.87, P < .001) for HELP unit patients discharged to home with or without services. Conclusion: The HELP program is associated with lower risk of 30‐day hospital readmission overall and for the subgroup of individuals discharged to home. Prospective studies are needed to confirm these observations.